Pembelajaran Berhitung Permulaan Melalui Permainan Balok Bergambar pada Anak TK: Studi Kasus TK Sukma Sejahtera Leuwiliang dan TK Islam Fatahillah Depok - Wiwi Uswatiyah; Sukamto Sukamto; Achmad Mudrikah; Ujang Cepi Barlian (Sekolah Pascasarjana Institut Agama Islam Nasional Laa Roiba Bogor, 2022)
Learning outcomes are influenced by several factors including the use of teaching aids by educators in the teaching and learning process. This study aims to analyze the ability to count, literacy, and creativity using educational games using number blocks at Sukma Sejahtera Leuwiliang Kindergarten, Bogor and Fatahilan Islamic Kindergarten, Depok. The research method used is a qualitative descriptive analysis method on the results of observations and assessments of class actions. Learning tools through educational games with number blocks are proven to be able to improve the mastery of numeracy comprehension in early childhood A in Sukma Sejahtera Leuwiliang Kindergarten, Bogor and Fatahilah Islamic Kindergarten. Relatively, the ability of teachers and students in Cycle II (TK Islam Fatahillah) was relatively better than the ability of teachers and students in Cycle I (TK Sukma Sejahtera). Literacy, creativity and innovation towards new methods are more important than institutional age.. Keywords: Counting, game tools, learning to count